2013
DOI: 10.1016/s0034-7094(13)70212-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Nociceptive, Analgesic and Pathohistological Effects of Intrathecal Dexmedetomidine and Bupivacaine in Rats

Abstract: There were no apparent pathohistological changes at least 24 hours after the intrathecal administration of a single dose of dexmedetomidine 3 μg and 10 μg. Dexmedetomidine added to bupivacaine for spinal block improves analgesia and prolongs block duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…DEX has been demonstrated to have significant analgesic effects ( 18–23 ). Although the mechanisms of the analgesic effect of DEX have not been fully elucidated, many studies have shown that DEX acted by inhibiting the release of substance P from the dorsal horn of the spinal cord ( 24,25 ). A recent study reported that DEX effected strong analgesia through inhibition of the spinal ERK1/2 signaling pathway ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…DEX has been demonstrated to have significant analgesic effects ( 18–23 ). Although the mechanisms of the analgesic effect of DEX have not been fully elucidated, many studies have shown that DEX acted by inhibiting the release of substance P from the dorsal horn of the spinal cord ( 24,25 ). A recent study reported that DEX effected strong analgesia through inhibition of the spinal ERK1/2 signaling pathway ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study done in animals showed significant analgesic effect and increased duration of the sensory and motor block when intrathecal dexmedetomidine was given along with bupivacaine. 22 The sensory block prolongation by intrathecal dexmedetomidine was by depressing the C-fibre transmitter release and also by postsynaptic dorsal horn neurons hyperpolarization. 23 Intrathecal dexmedetomidine prolong motor block by binding to α2 adrenoreceptors of motor neurons located in the spinal cord dorsal horn.…”
Section: Discussionmentioning
confidence: 98%
“…The analgesic effect of Dex-could be achieved with a high dose of 1 ug/kg over 10 min (26); however, to avoid anesthetic complications, our study used just 0.5 ug/kg of Dex-pre-anesthesia, and its effect on pain relief possibly originates from its sedation property. Current evidence suggests that Dex-acts by inhibiting the release of substance P from the dorsal horn of the spinal cord and the spinal ERK1/2 signaling pathway (27)(28)(29). A study by Park et al demonstrated that Dex-exerted a dose-dependent analgesic effect in rat models.…”
Section: Discussionmentioning
confidence: 99%